Developing Skills and Opportunities Of Future Primary Class Teachers - Muminjonova Muhayyo Gulomovna (Genius Journals, 2024)
The article contains information about the development of abilities and opportunities of future primary school teachers, issues of creativity, improving modern professional knowledge and creative abilities, conditions for the formation of creativity, principles of formation of educational content.
Keywords: Creativity; renewal of educational content; development of creative abilities